2023
DOI: 10.3389/fimmu.2023.1265818
|View full text |Cite
|
Sign up to set email alerts
|

The complementary roles of STAT3 and STAT1 in cancer biology: insights into tumor pathogenesis and therapeutic strategies

Weiyuan Wang,
Melanie Cristina Lopez McDonald,
Christine Kim
et al.

Abstract: STATs are a family of transcription factors that regulate many critical cellular processes such as proliferation, apoptosis, and differentiation. Dysregulation of STATs is frequently observed in tumors and can directly drive cancer pathogenesis. STAT1 and STAT3 are generally viewed as mediating opposite roles in cancer development, with STAT1 suppressing tumorigenesis and STAT3 promoting oncogenesis. In this review, we investigate the specific roles of STAT1 and STAT3 in normal physiology and cancer biology, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 111 publications
(40 reference statements)
1
4
0
Order By: Relevance
“…8 F). These results were consistent with previous reports showing that YTHDF1 gene deletion reduced STAT3 protein levels and phosphorylation, disrupted the STAT3-STAT1 balance in macrophages, promoted STAT1 expression and phosphorylation, and induced an anti-tumor polarization of macrophages [ 36 , 48 ]. Thus, our study provides valuable insights into the molecular mechanisms underlying the combination therapy and highlights its potential to enhance the efficacy of existing immunotherapies.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…8 F). These results were consistent with previous reports showing that YTHDF1 gene deletion reduced STAT3 protein levels and phosphorylation, disrupted the STAT3-STAT1 balance in macrophages, promoted STAT1 expression and phosphorylation, and induced an anti-tumor polarization of macrophages [ 36 , 48 ]. Thus, our study provides valuable insights into the molecular mechanisms underlying the combination therapy and highlights its potential to enhance the efficacy of existing immunotherapies.…”
Section: Resultssupporting
confidence: 93%
“…Reduction of STAT3 through pharmacological or genetic methods in many systems enhances STAT1 activation. This is because both STAT1 and STAT3 bind to the same phosphorylated tyrosine residues in signaling proteins such as gp130, leading to increased phosphorylation of STAT1 protein due to reduced competition at these sites [ 36 ]. MeRIP-qPCR analysis showed that STAT3 mRNA has significantly higher m6A enrichment levels in M2 macrophages compared to M1, indicating the regulatory role of YTHDF1 in the methylation of STAT3 mRNA and its impact on STAT3 protein translation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As noted earlier, STAT1 mediates the effects of IFNs and is a key component of the innate immune system response to viral infections and other pathogens [217]. Activated STAT1 can promote cell cycle arrest, apoptosis, differentiation, and enhanced immune recognition [6]. It can also mediate antiangiogenic effects [218].…”
Section: Chemical Biology Approachesmentioning
confidence: 92%
“…A key mediator of this effect, both in making tumor cells more visible to immune cells and activating immune cell function, are IFNs [185,186]. JAK inhibitors will generally suppress IFN signaling (which also uses JAK1, JAK2, and TYK2) and thus suppress critical immune effects [6]. This has also limited the clinical applicability of JAK inhibitors in cancer therapy.…”
Section: Targeting Upstream Kinases: Stat Phosphorylation As a Biomar...mentioning
confidence: 99%
See 1 more Smart Citation